Cross-Cultural Narrative through graphic stories In Polisario Refugee Camps (Revista Educação, Artes e Inclusão, 2020)
The Graphic Novel as a development of the last decades and nowadays an independent art form is presented in the context of workshop series within its educational potentials. Graphic story telling workshop series as methology exemplifies us an alternative form of communication beyond textual literacy. This took place within the framework of teacher training workshops in the Polisario refugee camps in Algeria. With the possibilities of the graphic novels, contents from the school environment and the everyday life of the participants were developed by means of art education, in the sense of a reflection of the own work event/ reference, for oneself and others. Drawings and personal stories from everyday life were developed in detail in the form of successive pictures and pictorial elements, sometimes including writing. In a non-verbal and playful way, the reality of life should come to face.   In particular, one's own experiential space should be experienced as a source of creativity - personal, original, self-referential should be appreciated and valued. Unconventional forms of communication were generated and established as mutually effective educational methods.
Keywords: Visual Interaction; Graphic Storytelling; Saharawi Refugee Camps